Blurred Vision in a Patient Suffering from Endometriosis and Epilepsy - Shushtarian, Seyed Mohammad Masoud; Shahmohammadi Dermani , Fereshteh; Pour Mazar, Reza (Journal of Ophthalmic and Optometric Sciences, 2021)
A 25-year-old lady was referred to Basir eye clinic for the visual evoked potential examination. Her medical history showed she had endometriosis and epilepsy, for which she used dienogest and carbamazepine. Certain drugs produce visual disturbances, which can be diagnosed based on the visual evoked potential examination.